Effect Of Structured Exercise Protocol VS Constraint Induced Movement Therapy on Shoulder Control in Post Stroke Individuals - Bhise, Riya Prashant; S.Anandh, S.Anandh (Journal of Neonatal Surgery, 2025)
Background: Strokes are a leading cause of disability, often resulting in persistent motor deficits, particularly in the upper limb and shoulder. Regaining shoulder control is crucial for functional independence and quality of life. While Constraint-Induced Movement Therapy (CIMT) and Structured Exercise Protocol (SEP) have shown promise in enhancing motor function post-stroke, their effectiveness on shoulder control specifically remains unclear. Methods: The sample size taken was 30 which was divided into 2 groups. Group A was given experimental treatment which included CIMT and conventional management. Group B was given only conventional management. The outcome measures used were STREAM and Fugl-Mayer scale. The pre and post assessment were taken on the first and last day respectively. The data was assessed using paired and unpaired t test for within and between the group analyses. Result: - The baseline values of both the groups didn’t show any statistical significant changes. But the post results of the experimental group showed a significantly large improvement in STREAM (p=0.03) and Fugl- Mayer Scale (p=0.01) results Conclusion: This study shows that post-stroke patients can benefit from both structured exercise protocols and constraint-induced movement therapy in terms of shoulder control. Nonetheless, the findings imply that CIMT might be more successful in improving shoulder control, especially with regard to range of motion and motor function.